Seasonality and Life History Complexity Determine Vulnerability of Dungeness Crab to Multiple Climate Stressors. Issue 4 (7th October 2021) - Berger, Halle M.; Siedlecki, Samantha A.; Matassa, Catherine M.; Alin, Simone R.; Kaplan, Isaac C.; Hodgson, Emma E.; Pilcher, Darren J.; Norton, Emily L.; Newton, Jan A.
Abstract: Scaling climate change impacts from individual responses to population‐level vulnerability is a pressing challenge for scientists and society. We assessed vulnerability of the most valuable fished species in the Northwest U.S.—Dungeness crab—to climate stressors using a novel combination of ocean, population, and larval transport models with stage‐specific consequences of ocean acidification, hypoxia, and warming. Integration across pelagic and benthic life stages revealed increased population‐level vulnerability to each stressor by 2100 under RCP 8.5. Under future conditions, chronic vulnerability to low pH emerged year‐round for all life stages, whereas vulnerability to low oxygen continued to be acute, developing seasonally and impacting adults, which are critical to population growth. Our results demonstrate how ontogenetic habitat shifts and seasonal ocean conditions interactively impact population‐level vulnerability. Because most valuable U.S. fisheries rely on species with complex life cycles in seasonal seas, chronic and acute perspectives are necessary to assess population‐level vulnerability to climate change. Plain Language Summary: The release of carbon dioxide (CO2 ) into the atmosphere by human activities is altering ocean conditions including pH, oxygen, and temperature. One way to understand how these changing conditions will affect ecologically, economically, and culturally important marine species is to scale individual responses from laboratory experiments to population‐level impacts. In this study, we assessed the vulnerability of Dungeness crab, one of the most valuable fisheries in the NW USA, to stressful conditions based on the predicted habitat exposure and response of each life stage (eggs, larvae, juveniles, and adults). The degree of vulnerability was determined by the seasonality of the ocean conditions in combination with the crab's complex life cycle. This approach revealed that Dungeness crab life stages and populations will be more vulnerable to low pH, low oxygen, and high temperature in the future (year 2100) under an aggressive CO2 emissions scenario. Based on these results, we recommend that fishery managers incorporate changing conditions into their decision‐making to protect vulnerable life stages in areas prone to stressful conditions (e.g., adult crabs in hypoxic areas). Our approach can be adapted for many other economically and ecologically important marine species in order to inform conservation and management strategies. Key Points: Dungeness crab vulnerability to future hypoxia is most severe overall due to increased exposure of the critical adult stage during upwelling The severity of vulnerability depends on the underlying spatiotemporal dynamics of ocean conditions and the crab's complex life cycle Our stage‐based and season‐sensitive approach is adaptable for many marine species with complex life histories that inhabit seasonal seas